The dynamic right-to-left translocation of Cerl2 is involved in the regulation and termination of nodal activity in the mouse node - Inacio, Jose Manuel (2018)
The determination of left-right body asymmetry in mouse embryos depends on the interplay of molecules In a highly sensitive structure, the node. Here, we show that the localization of Cerl2 protein does not correlate to its mRNA expression pattern, from 3-somite stage onwards. Instead, Cerl2 protein displays a nodal flow-dependent dynamic behavior that controls the activity of Nodal in the node, and the transmission of the laterality information to the left lateral plate mesoderm (LPM). Our results indicate that Cerl2 initially localizes and prevents the activation of Nodal genetic circuitry on the right side of the embryo, and later its right-to-left translocation shutdowns Nodal activity in the node. The consequent prolonged Nodal activity in the node by the absence of Cerl2 affects local Nodal expression and prolongs its expression in the LPM. Simultaneous genetic removal of both Nodal node inhibitors, Cerl2 and Lefty1, sustains even longer and bilateral his LPM expression.